Physical-Mechanical and Electrical Resistivity Properties of Cementitious Mortars Containing Fe3O4-MWCNTs Nanocomposite - Selen, Veyis; Guler, Omer; Nodehi, Mehrab; Sari, Ahmet; Yaras, Ali; Gencel, Osman; Ozbakkaloglu, Togay (Mdpi, 2023)
Recent growth in materials science and engineering technologies has pushed the construction industry to engage in new applications, such as the manufacturing of smart and electrically conductive products. Such novel uses of conductive construction materials would potentially allow their use in conjunction with various fields, such as those referred to as Industry 4.0. The following study uses iron oxide (Fe3O4)-multi-walled carbon nanotubes (MWCNTs) nanocomposites synthesized by chemical vapor deposition (CVD) and incorporated into the cementitious mortars as a substitute for sand at 1, 2, and 3% ratios to enhance the electrical conductivity. Results reveal that the electrical resistivity of cementitious composites decreases (due to the increase in electrical conductivity) from 208.3 to 61.6 & omega;& BULL;m with both the Fe3O4-MWCNTs nanocomposites ratio and the increasing voltage. The lowest compressive strengths at 7 and 28 days are 12.6 and 17.4 MPa for specimens with 3% Fe3O4-MWCNTs and meet the standards that comply with most applications. On the other hand, the highest porosity was reached at 26.8% with a Fe3O4-MWCNTs rate of 3%. This increase in porosity caused a decrease in both the dry unit weight and ultrasonic pulse velocity (from 5156 to 4361 m/s). Further, it is found that the incorporation of Fe3O4-MWCNT nanocomposites can have a negative effect on the hardening process of mortars, leading to localized air cavities and an inhomogeneous development of cementing products. Nonetheless, the improvement of the electrical conductivity of the samples without significantly compromising their physico-mechanical properties will allow their use in various fields, such as deicing applications with low-voltage electric current.
Keywords: electrically conductive mortars; chemical vapor deposition (CVD); multi-walled carbon nanotubes (MWCNTs); iron oxide (Fe3O4); characterization